Družbena odgovornost in trajnostni razvoj v slovenskih bankah - Glavič, Lucija (Management, 2025)
The article addresses the highly relevant issue of sustainable development and corporate social responsibility in the banking sector in Slovenia. Its purpose is to determine which material topics banks address when they talk about social responsibility and sustainable development; what are the expectations of stakeholders and society regarding this content and to compare these expectations with the actual activities of the banks. To achieve the purpose of the research and to answer the research question posed, we studied the relevant literature related to social responsibility and sustainable development in Slovenian banks, conducted an analysis of the annual reports of twelve Slovenian banks, and, within the research based on semi-structured interviews with nine representatives of the bank stakeholder groups, we obtained primary data, which we analysed using a content analysis method. The findings of the research indicate certain discrepancies between the relationship of banks and the expectations of their stakeholders in this area. This can serve as a guideline in the preparation of sustainability reports and strategies of banks in the future.
Keywords: bank stakeholders; banke; banks; corporate social responsibility; deležniki bank; družbena odgovornost; pomen posameznih vsebin; significance of individual topics; Slovenia; Slovenija; sustainable development; trajnostni razvoj